Effects of divergent angle on the flow behaviors in low speed wind accelerating ducts. (June 2020) - Ye, Jianjun; Cheng, Yanglin; Xie, Junlong; Huang, Xiaohong; Zhang, Yuan; Hu, Siyao; Salem, Shehab; Wu, Jiejun
Abstract: Combined with the negative pressure zone outside the duct, a new method based on the converging-diverging tube using for speeding up the low-grade wind is proposed in this paper. Firstly, a 3D CFD model of the converging-diverging air duct is developed, and the validation of the numerical model is also shown by comparing the experimental and numerical data. Secondly, based on the method of velocity stratification analysis at the air duct throat, the effect of the outlet angle on the speed increase is studied, and the mechanism of the negative pressure zone on changes to the wind speed is also analyzed and discussed. The air duct geometry was optimized, and the simulation study results were verified through experimental tests with a prototype duct and a wind tunnel. The results show that air ducts can significantly focus and increase wind speeds, offering insight for the future use low-speed winds for electricity generation. Highlights: The converging-diverging structure is beneficial to the wind speed accelerating. The negative pressure zone outside the duct will increase the wind velocity. The suitable outlet angle of the tube can increase 30% of the wind speed.